2015
DOI: 10.1037/xhp0000068
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral processing of gaze.

Abstract: When looking at someone, we combine information about their head orientation and eye deviation to judge their direction of gaze. What remains unknown, however, is how these cues combine when we are not looking directly at the person, but rather are using our peripheral vision. Given that peripheral vision helps direct future attention, understanding how we perceive other people's gaze is key to determining their future actions. To examine this, we asked participants to categorize gaze direction in faces whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 39 publications
6
31
1
Order By: Relevance
“…The faces in our investigation were much smaller by comparison (1.01° × 0.84°) and were available for unlimited inspection. These kinds of differences could reasonably be expected to influence the relative weighting of head and eyes in the computation of gaze, particularly if they impact the visibility or salience of these features (Florey, Dakin, Clifford, & Mareschal, 2015; Florey, Clifford, Dakin, & Mareschal, 2016; Gamer & Hecht, 2007). For example, information from the head might be weighted more heavily when a face makes a small image on the viewer’s retina, as when seen from a great distance.…”
Section: Discussionmentioning
confidence: 99%
“…The faces in our investigation were much smaller by comparison (1.01° × 0.84°) and were available for unlimited inspection. These kinds of differences could reasonably be expected to influence the relative weighting of head and eyes in the computation of gaze, particularly if they impact the visibility or salience of these features (Florey, Dakin, Clifford, & Mareschal, 2015; Florey, Clifford, Dakin, & Mareschal, 2016; Gamer & Hecht, 2007). For example, information from the head might be weighted more heavily when a face makes a small image on the viewer’s retina, as when seen from a great distance.…”
Section: Discussionmentioning
confidence: 99%
“…have observed sampling efficiencies at or below one for motion in children. Given that judging gaze direction of faces in the periphery is much poorer than in the fovea2022, it is not surprising that averaging gaze direction in a crowd of faces (most of which fall in the periphery) is also poor. The increase in effective sample size in the “large eyes” condition further supports this explanation of reduced peripheral resolution for the gaze condition.…”
Section: Discussionmentioning
confidence: 99%
“…who found that observers performed equally well on an emotion averaging task, regardless of whether information was available around fixation or not. It is possible that this may reflect differences in the stimuli used; peripheral emotion can be perceived with some degree of accuracy49 whereas peripheral gaze cannot2122. Alternatively, it may be the case that observers alter their sampling strategy to adapt to the structure of the image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this integrative process can be quite linear (at least with adults; Otsuka, Mareschal, & Clifford, ), it is also known to be flexible at the group level, with non‐linear weighting for particular combinations of head and eye rotations (Sweeny & Whitney, ) or according to each feature's salience or visibility (Florey, Clifford, Dakin, & Mareschal, ; Florey, Dakin, Clifford, & Mareschal, ). Flexible weighting across changing circumstances makes sense, but how variable might this process be on an individual basis?…”
Section: Introductionmentioning
confidence: 99%